IMPACTS OF VOCATIONAL PROGRAMMES IN CHILDREN CORRECTIONAL CENTRE, UGBEKUN, BENIN CITY, EDO STATE, NIGERIA - Ohiomah, Ajayi; Efejuku, Amorighoye Deston (African Journal of Social and Behavioural Sciences, 2024)
This study examined the impacts of vocational programmes on juvenile offenders in the Children Correctional Centre, Ugbekun, Benin City. The study reviewed existing studies on the impacts of vocational programmes in children correctional centres. The research used a qualitative approach, with 30 participants through purposive sampling. Appropriate data were collected through in-depth interviews and focus group discussions. The participants, all first-time offenders, had been arrested for various crimes, including theft, rape, possession of weapons and attempted murder. The study showed that effective vocational programmes lead to positive behavioural changes and successful reintegration into society, making juveniles self-sufficient and content. The findings suggest that vocational programmes reduce recidivism, unlike mere incarceration. The study recommends that correctional staff receive more training in rehabilitation techniques, the facilities be improved, and the government work with stakeholders to provide better funding and resources for the vocational programmes.